Scholarship and Partisanship Essays on Max Weber. - Bendix, Reinhard (University of California Press, 2022)
Today, Max Weber appears to many younger academic rebels as the patron sait of ""value neutral"" social science, yet he too engaged in a furious generational rebellion of his own, and in the end chose science as a vocation. These essays deal with Weber's substantive and methodological contribution and the relation of his life to his place in intellectual and political history. They examine the influences on Weber, as well as his similarities to and differences.